Reduction of Chromium and Manganese Heavy Metal Concentration in Leachate by Electrocoagulation - Tricia Danica C. Calma; Micaela Angela T. Derramas; Joseph R. Ortenero; Ian A. Navarrete; Allan N. Soriano (Chemical Engineering Transactions)
Landfill leachate is a notorious problem. It possesses high toxicity levels of heavy metals that can cause severe danger and threat to human health. Electrocoagulation is used in this work to treat landfill leachate at Payatas dumpsite in Quezon City, Philippines. The electrocoagulation process is an electrochemical method that treats wastewater, which can potentially remove heavy metal pollutants from the leachate. The concentrations of Cr and Mn in the samples are reduced, resulting in an acceptable removal rate of 71.25 % for Cr and 74.95 % for Mn. Results also indicate that increasing the voltage supply and electrocoagulation time increases the removal rate of the heavy metals. The highest removal rate for both Cr and Mn heavy metal concentration is achieved at pH 5, 8 V applied potential, and 90 min electrolysis time. These optimized values of the parameters result in the high removal efficiency of heavy metals found in the leachate. The results of this work could be used in the management of leachate at the Payatas dumpsite before it reaches surrounding bodies of water. It could also be replicated in other landfill facilities in the country for the sustainable treatment of other heavy metals through the integration of an electrocoagulation setup with renewable energy sources.